PENERAPAN MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION UNTUK MENINGKATKAN KEMAMPUAN MATEMATIS - Putri Saron Mallini; Santri Chintia Purba; Hotmaulina Sihotang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Mathematics learning is designed to achieve the objective of mathematics learning, that is to stimulate students to grow their mathematical abilities. However, the activities of teaching-learning have been applying the conventional learning method, in which the teacher has full control of learning so that students' mathematical abilities are classified as low. The learning model that is applied to the solution to improve students' mathematical abilities is Student Team Achievement Division (STAD). This research involved VIII classes of SMP Negeri 50 Jakarta, which are VIII-B and VIII-D classes using a Quasi-Experimental Design. Data collection was based on a pretest, posttest, and gain data by statistical test through the Mann-Whitney U test by the calculation of the program SPSS 26 because the data is not a normal distribution and not homogeneous so that it is obtained that: (1) There is a difference in mathematical ability between students who apply STAD and Expository learning models. The average posttest score of mathematical ability between students with the STAD learning model treatment is superior to the Expository learning model, that is 66,64 and 15,78. (2) There is a difference in improving mathematical ability between students who apply the STAD and Expository learning models. The average gain score of mathematical ability between students who apply the STAD learning model is superior to the Expository learning model, that is 64,56 and 13,08.